Exploring the Socioeconomic Factors and Causes of In-Migration: A Study on Rainas Municipality, Lamjung District (Pragyaratna प्रज्ञारत्न, 2023)
The main causes of migration of that place were for higher education and employment. Migrant people left their home mainly in search of employment. The proportion of dependent migrants was higher than proportion of migrants involved in economic activity. The main objective of the study is to find out the situation, nature and causes of migration and explore the patterns of remittance from migration. The migrants were mostly students and unemployed adult population for searching jobs. The highest migration by ethnic Caste groups were Brahman and Dalits. The highest caste-wise remittance entered Dalits and Gurung and the highest amount of remittance was used for buying land in this place.